A Critique of the Book the History of Arabic Literature in Hadith Era - Mohsen Seifi; Bahare Samadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book “the History of Arabic Literature in Hadith Era” written by Nader Nizam Tehrani is about the history of Arab contemporary literature. In this book, by considering contemporary literary events and movements and also pointing to the poets of the era, the author tries to present an overall picture of Arab literary life. The study of the book shows that like other written works, this book cannot be considered the best of its kind and has some deficiencies which should be resolved in the next editions. In this article, by considering different dimensions of the work, taking an impartial approach and applying logical principles necessary for a scientific critique, the author tries to see to what extent the original writer (of the book) had adhered to the scientific standards of writing, and how he has used them to realize pedagogical goals. Furthermore, by evaluating the book as a pedagogical resource, the author of the article will determine to what extent it holds the features of a technical and specialized work.